1965
DOI: 10.1146/annurev.bi.34.070165.000533
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins

Abstract: Isolation and structure determination,-In 1933-1934 Goldblatt (1, 2) and von Euler (3) independently demonstrated that extracts of human seminal plasma and of the vesicular gland of sheep produce a fall in blood pressure and stimulate a variety of smooth muscle organs. The active material was named prostaglandin by von Euler, who also showed that it was lipid soluble and had acidic properties (4-7).In 1957 Bergstrom & Sjovall isolated two crystalline compounds from the vesicular gland of sheep (8-10). One of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Although they serve as important precursors for prostaglandin synthesis (Bergstrom, 1966), unsaturated fatty acids may also share equally crucial roles as receptor signals. For example, linoleic and arachidonic acids activate PPARa with a potency of 30 ,tM (Gottlicher et al, 1992;Banner et al, 1993;.…”
Section: Phytol Metabolites As Transcriptional Signalsmentioning
confidence: 99%
“…Although they serve as important precursors for prostaglandin synthesis (Bergstrom, 1966), unsaturated fatty acids may also share equally crucial roles as receptor signals. For example, linoleic and arachidonic acids activate PPARa with a potency of 30 ,tM (Gottlicher et al, 1992;Banner et al, 1993;.…”
Section: Phytol Metabolites As Transcriptional Signalsmentioning
confidence: 99%
“…In any case, such a propensity to form the most unsaturated cholesteryl esters must explain their relative abundance in the adrenal cortex. Furthermore, the accumulation of these esters might be a means of storing arachidonic acid which is a precursor of the prostaglandins (29); the latter in turn might regulate the adrenal vasculature and blood perfusion; by their ACTH-like effects the prostaglandins might also exert a more direct control on steroid hormone production (30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite centuries of use, the action mechanism of acetylsalicylic acid (Aspirin) was not described until 1971 by Sir John Vane 1 who showed that acetylsalicylic acid was an inhibitor of prostaglandin synthesis (Vane, 1971). At this time, the prostaglandins 2 had already been structurally characterized by Sune Bergström and Bengt Samuelsson (Bergström, 1967;Bergström and Samuelsson, 1965;Samuelsson, 2012) making it possible to identify PGE as an inflammatory prostaglandin.…”
Section: Immune-to-brain Signalingmentioning
confidence: 99%